Rancang Bangun Sistem Monitoring Pengukuran Volume Air Berbasis IoT Menggunakan Arduino Wemos - Muhamad Yusup; Po. Abas Sunarya; Krisandi Aprilyanto (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
System The process of counting and storing in a manual water reservoir analysis has a high percentage of error rate compared to an automated system. In a company industry, especially in the WWT (Waste Water Treatment) section, it has several reservoir tanks as stock which are still counted manually. The ultrasonic sensor is placed at the top of the WWT tank in a hanging position. Basically, to measure the volume in a tank only variable height is always changing. So by utilizing the function of the ultrasonic sensor and also the tube volume formula, the stored AIR volume can be monitored in real time based on IoT using the Blynk application. From the sensor, height data is obtained which then the formula is processed by Arduino Wemos and then information is sent to the MySQL database server via the WIFI network.